Comparison of the performance and risk diversification benefits of government linked companies (GLCS) Malaysia and Singapore - Lim, Brian Zee Yi (2019)
This study examines and compares the investment performance and risk diversification benefits of Government Linked Companies (GLCs) in Malaysia (MGLCs) and Singapore (S-GLCs) by using the tried and tested performance measures, namely the Sharpe Ratio, Treynor Ratio and Jensen’s Alpha to assess their investment performance and the Diversifiability Measure (proportion of unsystematic risk to total risk OR one-minus R-squared) to assess risk diversification benefits. The study period for both M-GLCs and S-GLCs extends from 2009 to 2018 to provide a direct and straightforward 10-year comparison. The results show that M-GLCs perform better than S-GLCs in terms of Sharpe ratio and Treynor ratio, but slightly worse in terms of Jensen’s Alpha. The total risk of SGLCs is higher than M-GLCs, while the Beta values for both M-GLCs and S-GLCs are less than one, implying that GLCs in both countries are less risky when compared against their respective national market indexes. M-GLCs have lower RSquared values than J-GLCs, which suggests that M-GLCs are not as diversified than S-GLCs and therefore, M-GLCs have more opportunities for diversification. The Diversifiability Measure calculated for M-GLCs are higher than S-GLCs and suggests that M-GLCs have better risk diversification benefits. This study aims to expand on research into GLCs as well as help investors to make more informed investment decisions when considering the addition of M-GLCs and S-GLCs into their portfolios. Best and worst performers among the M-GLCs and S-GLCs are also determined in this study. This study will provide investors with greater knowledge and insight into the actual real-world investment performance and risk diversification benefits of including M-GLCs and/or S-GLCs into their portfolios.